Political behaviour affect job performance / Mohamad Huzaifah Hamdan - Hamdan, Mohamad Huzaifah (2017)
The purpose of this research is to determine the relationship between organizational politic and trust among employees at Department of Occupational Safety and Health (Sarawak Branch). The respondents are selected from the officer in all departments in Kuching, Sibu, Bintulu and Miri branch. There are ten sections in this chapter. It discusses the problem statement, research objectives, scope of the study, conceptual framework, significance of the study, limitations of the study, definition of terms and a briefly summary of this chapter.